The research of acute toxicity of 4-amino-5-(4-(tert-butyl)phenyl)-4H-1,2,4-triazoles-3-thiol derivatives - I. I. Аksyonova-Seliuk; Ye. S. Pruglo; O. I. Panasenko; Ye. G. Knysh (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Introduction. The process of new drugs creating includes a plurality of stages, which allow their application in medical practice in the future. These studies are a guarantee of the effectiveness and safety of the test compounds. One of the most important stages of preclinical research is the research of acute toxicity. The data of this experiment gives an estimate of toxic effect of new compounds on the organism of experimental animals that allows to judge about expediency of application of these substances in diseases therapy.